Clinical Cases in Neonatal and Infant Dermatology - Arcangeli, Fabio; Lotti, Torello M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is a concise practical guide designed to facilitate the clinical decision-making process in the management of neonates and infants. Dermatologists and general pediatricians who offer primary care to children must be knowledgeable in managing pediatric dermatological problems, and this title provides insightful reviews of a number of common and rare dermatologic cases. Clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual cases using best practice techniques. Pediatric dermatology is a particularly important discipline in this regard since it is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria to base their clinical decision-making on. Clinical Cases in Neonatal and Infant Dermatology concisely covers how to approach diagnosing and managing skin disease in the very youngest patients. Each chapter focuses on a particular case and emphasizes how to make an appropriate choice when deciding which diagnostic tool or management strategy would be most suitable. Potential complications are detailed and management tips provided to enable the reader to develop a deep understanding of how approach the care of these patients within their day-to-day clinical practice. This book therefore represents an ideal up-to-date resource for all practitioners who encounter these conditions as part of their everyday practice.
A infant with generalized pimples and nodules -- A newborn with a large facial segmental vascular lesion -- A newborn with several white spots on the forehead -- A one-and-a-half-month-old boy with recurrent fever, heat intolerance and diminished sweating -- Acrodermatitis Enteropathica in a 7-month-old baby boy -- An 11-month-old child with a nodular lesion on her right buttock -- An eczematous lesion on the forehead of a three-month-old child -- An infant with disseminated red scaling papules -- Axillary Dermatitis in a newborn -- Baby girl with widespread lesions on the face and alopecic nodules of the scalp -- Benign Cephalic Histiocytosis -- Congenital skin scars -- Cryotherapy Treatment in Infantile Hemangioma -- Epidermolytic ichthyosis -- Incontinentia Pigmenti With Ocular Involvement -- Infantile erythroderma caused by focal infection -- Infantile hemangioma: successful treatment with topical treatment -- Infantile Type Atopic Dermatitis -- Kasabach-Merritt Syndrome -- Oral Isotretinoin Treatment Of Harlequin Ichthyosis -- Oral Propranolol Treatment for Infantile Hemangioma -- Perianal dermatitis -- Skin manifestation in congenital syphilis: a serial cases -- Staphylococcal Scalded Skin Syndrome -- Subcutaneous indurated plaques in a newborn -- Vesicles on the tongue of a 3-month-old baby -- A 1-year-old boy with multiple papules -- A Case of High Risk Multisystem Langerhans Cell Histiocytosis in 22 Months Old Boy -- A Case with erythema, scales and itching.
Keywords: Dermatology; Dermatology; Infant -- diseases